Calculation method of shading area covering southerly orientated windows for the Tangwu building in Sizhai village. (1st March 2019) - Chi, Fang'ai; Zhu, Zongzhou; Jin, Lei; Bart, Dewancker
Highlights: Taking traditional dwellings in the east of Zhejiang as research objectives. Calculation equations of shading area covering windows were formulated. Shading performances are the most outstanding on the summer solstice. Eave and corridor play the largest roles in regulation of solar radiation. Abstract: The Tangwu building is one of the most important type of houses in Chinese traditional dwellings. The shading performances on the windows installed in southerly orientated wall of the Tangwu building are of a significant impact on indoor thermal and visual comforts for its occupants. Taking traditional dwellings situated in the east of Zhejiang province as research objectives, the calculation equations for shading areas generated by eave and corridor, the East-wing-room building and West-wing-room building, as well as the Hall-room building covering southerly orientated windows of the Tangwu building were formulated, respectively. In terms of the Tangwu building orientation, three kinds of building orientations, that is directly south, southeast and southwest, were taken into account in the process of equation formulation. Taking Faxiangju villa in Sizhai traditional village as a case study, its shading performance during daytime on the summer solstice, autumnal equinox, and winter solstice were analyzed by calculating shading areas and shading ratios using the formulated equations. Research results reveal that the eave and corridor, classified as a horizontal shading device system, play the largest roles in the management and adjustment of solar ray penetrating through windows. Furthermore, the shading ratios present a gradually decreasing trend from the summer solstice to the autumnal equinox, and then to the winter solstice. In contrast, the shading ratios gradually increase during a period of time that extends from the winter solstice to the vernal equinox, and then to the summer solstice. It presents a cyclical process that takes one year to complete.